Design and construction of a three‐dimensional electrode with biomass‐derived carbon current collector and water‐soluble binder for high‐sulfur‐loading lithium‐sulfur batteries. Issue 4 (2nd June 2020) - Wang, Pengfei; Gong, Zhe; Ye, Ke; Kumar, Vipin; Zhu, Kai; Sha, Linna; Yan, Jun; Yin, Jinling; Cheng, Kui; Wang, Guiling; Cao, Dianxue
Abstract: Lithium‐sulfur batteries attract lots of attention due to their high specific capacity, low cost, and environmental friendliness. However, the low sulfur utilization and short cycle life extremely hinder their application. Herein, we design and fabricate a three‐dimensional electrode by a simple filtration method to achieve a high‐sulfur loading. Biomass porous carbon is employed as a current collector, which not only enhances the electronic transport but also effectively limits the volume expansion of the active material. Meanwhile, an optimized carboxymethyl cellulose binder is chosen. The chemical bonding restricts the shuttle effect, leading to improved electrochemical performance. Under the ultrahigh sulfur load of 28 mg/cm 2, the high capacity of 18 mAh/cm 2 is still maintained, and stable cycling performance is obtained. This study demonstrates a viable strategy to develop promising lithium‐sulfur batteries with a three‐dimensional electrode, which promotes sulfur loading and electrochemical performance. Abstract : Carbonized biomass has a unique array‐like straight tube structure that effectively limits the volume expansion of sulfur during discharge. The slurry formed by mixing the aqueous binder and S is drawn into the self‐supporting carbon sheet by a vacuum suction method. This design can greatly improve the capacity and cycle performance of the electrode at high S loading.